2021
DOI: 10.1177/11786388211039427
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Knowledge is Associated With the Consumption of Iron Rich Foods: A Survey Among Pregnant Women From a Rural District in Northern Ghana

Abstract: Introduction: Iron deficiency anaemia is an international public health concern and pregnant women are at an increased risk. We investigated the consumption of iron rich foods and associated factors among pregnant women in a rural district from Ghana. Methods: Following a cross-sectional design, dietary intake of iron rich foods was obtained from 252 pregnant women using a 24-hour recall food check list. Nutrition knowledge, attitudes and socio-demographic characteristics were also assessed. Findings: Particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…This study, however, discovered that women had low frequency of intake of iron-rich meals such as meat, green leafy vegetables and fruits, which are high in vitamin C to promote iron absorption, leading to anaemia. Adjei-Banuah et al. (2021) found comparable results in pregnant women in northern Ghana.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…This study, however, discovered that women had low frequency of intake of iron-rich meals such as meat, green leafy vegetables and fruits, which are high in vitamin C to promote iron absorption, leading to anaemia. Adjei-Banuah et al. (2021) found comparable results in pregnant women in northern Ghana.…”
Section: Discussionmentioning
confidence: 53%
“…This study, however, discovered that women had low frequency of intake of iron-rich meals such as meat, green leafy vegetables and fruits, which are high in vitamin C to promote iron absorption, leading to anaemia. Adjei-Banuah et al (2021) found comparable results in pregnant women in northern Ghana. The high rate of anaemia in pregnant women in the research suggests micronutrient deficiency, a major public health issue in underdeveloped nations (Shubham et al, 2020).…”
Section: Anaemia and Dietary Diversitymentioning
confidence: 53%
“…A study carried out in Northern Ghana with 252 pregnant women investigated their knowledge regarding iron deficiency anemia and their eating habits. The findings revealed a positive correlation between knowledge and practices as the knowledge scores were significantly associated with an iron-rich diet [12]. An intervention study in India showed that a sixmonth education intervention targeting adolescent girls significantly improved not only their knowledge about IDA but also their health practices such as taking their supplements and checking their hemoglobin levels [13].…”
Section: Introductionmentioning
confidence: 93%
“…Further, a study in Jordan showed an association between maternal educational level and hemoglobin levels among pre-school children aged 36 to 59 months and found their diet to be low in foods that enhance iron absorption but high in foods that inhibit iron absorption [ 21 ]. A lack of knowledge of mothers on an adequate, nutrient-rich diet for themselves and their offspring can be an important contributor to child anemia [ 22 , 23 , 24 ]. According to a study undertaken in Beirut, Lebanon (2016), the majority of Syrian refuge women were not knowledgeable about maternal nutrition, half of the women had inadequate dietary practices during pregnancy and a quarter of the women had a negative attitude towards antenatal care [ 25 ].…”
Section: Introductionmentioning
confidence: 99%